The multi-agent system architecture in SEWASIE - Fillottrani, Pablo Rubén (2005)
We describe the design, implementation and deployment of the multi-level agent-based system architecture developed for the SEWASIE project. The aim of the system is to help the user in querying heterogeneous data sources which are integrated by means of ontologies. The agent architecture is based on a two level data integration scheme supported by mediators and brokers, connected by a peer to peer mechanism. Implementation is done on top of the JADE system, a modular and scalable platform that satisfies FIPA standards.